2018
DOI: 10.1038/s41598-018-27428-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of disorder when upscaling magnetocaloric Ni-Co-Mn-Al Heusler alloys from thin films to ribbons

Abstract: Research in functional magnetic materials often employs thin films as model systems for finding new chemical compositions with promising properties. However, the scale-up of thin films towards bulk-like structures is challenging, since the material synthesis conditions are entirely different for thin films and e.g. rapid quenching methods. As one of the consequences, the type and degree of order in thin films and melt-spun ribbons are usually different, leading to different magnetic properties. In this work, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 47 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…The as-cast samples were wrapped by tantalum foil and annealed in a high-vacuum quartz tube at 1173 K for 96 h, followed by quenching in ice water. It is noted that the effect of different heat treatments on the magnetic and magnetocaloric properties has been studied intensively in NiMn-based Heusler alloys [22][23][24][25]. It is revealed that the MCE can be largely improved by optimizing the heat treatment, e.g., an optimized annealing method can reproduce the excellent functional properties of Ni-Co-Mn-Al films in ribbons [25].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The as-cast samples were wrapped by tantalum foil and annealed in a high-vacuum quartz tube at 1173 K for 96 h, followed by quenching in ice water. It is noted that the effect of different heat treatments on the magnetic and magnetocaloric properties has been studied intensively in NiMn-based Heusler alloys [22][23][24][25]. It is revealed that the MCE can be largely improved by optimizing the heat treatment, e.g., an optimized annealing method can reproduce the excellent functional properties of Ni-Co-Mn-Al films in ribbons [25].…”
Section: Methodsmentioning
confidence: 99%
“…It is noted that the effect of different heat treatments on the magnetic and magnetocaloric properties has been studied intensively in NiMn-based Heusler alloys [22][23][24][25]. It is revealed that the MCE can be largely improved by optimizing the heat treatment, e.g., an optimized annealing method can reproduce the excellent functional properties of Ni-Co-Mn-Al films in ribbons [25]. Here, we chose the same heat treatment from Reference [17], which also studied Ni 50 Mn 34 Co 2 Sn 14 and presented giant MCE in this alloy.…”
Section: Methodsmentioning
confidence: 99%
“…We also mix Mn with Fe in Co 2 (Mn 1−x Fe x )A, where A is Sn or Sb, and 0 ≤ x ≤ 1. We show that in fH Co 2 MnX alloys, the width of the minority-spin band gap E gap decreases along the period (3)(4)(5)(6) and increases along the group (13-16) of X.…”
Section: Introductionmentioning
confidence: 81%
“…Heusler alloys [1] are a large class of naturally occurring [2] and manufactured [3] ternary intermetallic compounds with L2 1 full Heusler (fH) or C1 b half-Heusler (hH) structure (sometimes called semi-Heusler), which can be partially disordered [4][5][6][7][8][9][10]. Many Heuslers are ferromagnetic (FM), with Curie temperatures T c between 200 and 1100 K [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…A special class of magnetic shape memory alloys are Heusler compounds such as NiMnX (X = Al, Ga, Sn, In), which are considered as promising materials for magnetocaloric cooling applications due to their magnetoelastic coupling near room temperature [10][11][12]. However, most of the compounds show a large thermal hysteresis, which limits their potential in future applications [13][14][15]. Therefore, efficient mechanisms to change the martensitic transformation behavior have to be identified.…”
Section: Introductionmentioning
confidence: 99%